Photocatalysis of glycerol over Pt/TiO2 catalyst - Nuraini, Nurazaman (2013)
Glycerol is produced as waste by-product in solution form during the transesterification process and potentially detrimental to the environment. Hence, photocatalysis was employed in the current work for the treatment of glycerol waste using UV light activated Pt/TiO2 photocatalyst. The reaction was carried out under ambient conditions. The experimental work was devided into (i) preparation and characterization of the catalyst and (ii) photoreforming reaction. 5% Pt/TiO2 was prepared. From the X-Ray diffraction analysing, the XRD pattern of the Pt/TiO2 was essentially similar to that of TiO2 sample (anatase type). The absence of diffraction lines of Pt phase on the 5% Pt/TiO2 catalyst indicates that platinum was well dispersed in the crystalline matrix. The specific surface area for 5% Pt/TiO2 is 23.60m2/g and for TiO2 is 12.92m2/g. It was recorded 80% improvement in Pt-doped TiO2 catalyst analysed by using BET. The effects on the glycerol concentration show that when the concentration increased, the absorption of uv-light was decreased. From the kinetic study, the reaction determined was zero-order reaction with the -k value is equal to 9.5. The rates of glycerol converted to syngas were shown in the results of COD analysing. Through this research, the result obtained shows the photodecomposition of glycerol occurred under uv-light.